2008
DOI: 10.3174/ajnr.a1269
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Outcome of Pulmonary Polymethylmethacrylate Embolism during Percutaneous Vertebroplasty

Abstract: BACKGROUND AND PURPOSE:During percutaneous polymethylmethacrylate (PMMA) vertebroplasty (PV), PMMA cement may migrate into the venous system and subsequently be transported to the pulmonary arteries. Frequency, outcome, and imaging findings of PMMA pulmonary embolism are poorly understood. We retrospectively assessed the frequency and outcome of PMMA embolism during PV in a large patient cohort and evaluated the relationship of the volume of injected PMMA to the occurrence of pulmonary PMMA embolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 18 publications
3
64
0
6
Order By: Relevance
“…A previous study showed that PCE occurred infrequently and caused no pulmonary reaction on CT after 1 year. 9 In our study, cement in the azygos vein on postprocedural CT of the treated vertebrae was the only risk factor for PCE. Analogously, other studies 13,14 showed a statistically significant relation between PCE and cement leakage into the inferior caval vein.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…A previous study showed that PCE occurred infrequently and caused no pulmonary reaction on CT after 1 year. 9 In our study, cement in the azygos vein on postprocedural CT of the treated vertebrae was the only risk factor for PCE. Analogously, other studies 13,14 showed a statistically significant relation between PCE and cement leakage into the inferior caval vein.…”
Section: Discussionmentioning
confidence: 45%
“…7,8 In most studies with a low incidence of PCE, "the occurrence of PCE" is defined as cement migration toward the lungs observed during fluoroscopy. 9 In studies with standard postprocedural chest radiographs, the observed incidence is higher 10,11 ; apparently, a substantial proportion of PCE remains undetected during fluoroscopy. In 1 study, the long-term effects of pulmonary cement deposits on the surrounding lung parenchyma are largely unknown.…”
mentioning
confidence: 99%
“…PMMA can leak through segmental veins into the inferior vena cava and reach the lungs. This is a well-known complication of vertebroplasty [15,16]; yet, alarming as it may seem, it is usually sub-clinical with very rare short-or long-term implications [15]. If routine chest CT scanning is done after the procedure, 23% of vertebroplasty patients are found to have pulmonary PMMA emboli [16], apparently with no sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…The cement application, however, is comparable to its use in vertebroplasty and kyphoplasty, 49 and leakage rates might be comparable too. Cement leakage rates in vertebroplasty and kyphoplasty are reported to be between 19.3% 47 and 80%, 46 but they are usually above 40%. 9,22,24,32,36,44,48,49 The reason for high leakage rates in cadaver models might be the missing venous counter-pressure, 6 but this does not explain high leakage rates during surgery.…”
Section: 4%mentioning
confidence: 99%